Perceived Psychological Health Impact Caused By Work-Related Communication After Working Hours Among Lecturers: A Case Study - Nurul Nazirah, Hamzah (2025)
Professional contacts have changed dramatically because of the increasing use of digital communication technologies, especially WhatsApp, but the lines between work and personal life have also become hazier. The psychological effects of academicians at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) using WhatsApp for work-related purposes beyond office hours are investigated in this study. A cross-sectional survey was used to gather information from 30 academics about how they felt about communication after hours and how it affected their mental health. To measure psychological consequences, the Depression, Anxiety, and Stress Scale (DASS-21) was utilised. The findings show that 56.7% of respondents said they received work-related communications on vacations, 70% said they received them on weekends, and 86.7% said they received them when off-duty. Remarkably, 30% of participants thought that after-hours communication had a detrimental effect on relationships with coworkers, and 33.3% of participants found it to be stressful. Significant correlations between mental health outcomes and variables like income level, chronic illness, and job grade were found through analysis; participants with chronic conditions and those with higher job grades were more susceptible to stress, anxiety, and depression. The findings highlight the urgent need for institutional interventions, including policies to limit after-hours communication, flexible work arrangements, and accessible mental health support. Such measures aim to mitigate stress and promote work-life balance, ensuring a healthier professional environment for academicians. This study contributes to the growing discourse on the psychological implications of digital connectivity in academia and offers actionable strategies to support mental health and well-being in educational institutions.